Accumulating Partial Products

If we let A = 1 initially, then the steps of the iteration are:
  n! = A × n × (n-1) × (n-2) × ... × 2 × 1
       -----
	 |
    Call this A

     =     A × (n-1) × (n-2) × ... × 2 × 1
       	   ---------
	       |
          Call this A

     =            A  × (n-2) × ... × 2 × 1
                     .
                     .
     =                               A × 1

     =                                   A
At each step, we made use of the fact that
	 A × B! = (A × B) × (B-1)!
So at the end, A = n!